ELIMINASI WASTE PADA LINI ASSEMBLY DI PT. X DENGAN PENDEKATAN LEAN MANUFACTURING - Diah Arum Puspita (2022)
PT. X is an energy manufacturing industrial companies that designs and produce hardware, controls system and cable anchoring. One of the product is the Spacer. Upon assembling the Spacer , there is still waste found in the work activity, therefore identification is needed to reduce or eliminate activities that are considered waste. The purpose if this research was to identify and provide suggestions for improvements to reduce or eliminate waste using lean manufacturing approach and to design a better production system by simulating the system with Flexsim software based on the proposed improvements that have been given. Based on the identification result, the dominant waste are proven to be on the process of waiting, transportation, motion and defects. The lean manufacturing tools used in this research are Value Stream Mapping (VSM) and Value Stream Analysis Tools (VALSAT), then identify the potentian problem, used Failure Mode Effects Analysis (FMEA) and Simulation Model Design. Based on the data processing using tools mentioned above, the researcher obtained recommendations for improvements that can reduce lead time by 21.22 hours.